SISTEM KONTROL SUHU AIR AQUARIUM UNTUK IKAN MENGGUNAKAN SENSOR SUHU BERBASIS ARDUINO UNO - Nebokat Nezhar; Asep Wasid (Universitas Methodist Indonesia, 2026)
An aquarium serves as a container designed to house and display various aquatic organisms and elements. For aquascape enthusiasts, maintaining cleanliness and stable environmental conditions within the aquarium is essential to preserve the beauty and health of both fish and aquatic plants. However, using water cleaners alone is insufficient, as temperature is a crucial factor that affects the comfort and survival of aquatic organisms. Considering that Indonesia experiences two distinct seasons, which can cause fluctuations in water temperature, a system capable of automatically controlling the temperature is required. This research aims to design a Water Temperature Control System for Aquarium Fish Using a Temperature Sensor Based on Arduino Uno. The system is developed to help aquascape hobbyists maintain a stable water temperature without manual intervention, allowing the temperature to automatically adjust according to the needs of the fish. The Arduino UNO microcontroller serves as the main component, integrated with a DS18B20 temperature sensor, a mini fan, and a push button. The temperature data detected by the DS18B20 sensor are displayed on an OLED LCD screen, which is programmed using the Arduino IDE. This system enables efficient and accurate water temperature regulation, ensuring a stable environment that supports the well-being of fish and aquatic plants within the aquarium.